Comparison of hormonal levels in ovarian follicular fluid of normal versus subfertile buffaloes - Honparkhe, Mrigank; Gandotra, Vinod Kumar; Ghuman, Sarvpreet Singh; Matharoo, J S; Brar, Parkash Singh (The Indian Journal of Animal Reproduction, 2022)
Six normal cycling and fifteen subfertile buffaloes were subjected to transvaginal ultrasound guided aspiration of ≥5 mm size follicles and the follicular fluid was collected on each occasion to estimate the levels of progesterone, estradiol and IGF-1. The follicles were categorized and pooled according to their size as 5 to 6, >6-8 and >8 mm. In normal cycling buffaloes, estradiol and IGF concentration increased (P<0.05) as the follicular size increase whereas the progesterone concentration varied non-significantly among the different size categories of follicles. In subfertile buffaloes, the concentrations of progesterone, estradiol and IGF-1 remained similar among different follicular diameter ranges. However, the concentrations of various hormones in different size categories were significantly (P<0.05) higher in subfertile than that in normal cycling buffaloes. In conclusion, subfertile buffaloes had unchanged concentrations of hormones among different size categories indicating disturbed steroidogenesis and require further investigations.